2017
DOI: 10.3390/v9110335
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Full-Length Feline Immunodeficiency Virus Capsid Protein Shows an N-Terminal β-Hairpin in the Absence of N-Terminal Proline

Abstract: Feline immunodeficiency virus (FIV) is a member of the Retroviridae family. It is the causative agent of an acquired immunodeficiency syndrome (AIDS) in cats and wild felines. Its capsid protein (CA) drives the assembly of the viral particle, which is a critical step in the viral replication cycle. Here, the first atomic structure of full-length FIV CA to 1.67 Å resolution is determined. The crystallized protein exhibits an original tetrameric assembly, composed of dimers which are stabilized by an intermolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 53 publications
(78 reference statements)
2
33
0
Order By: Relevance
“…The FIV CA-NTD model obtained from SWISS-MODEL and the FIV CA-CTD crystal structure (PDB accession number 5DCK [18]) were separately aligned with HIV-1 CA structure (PDB accession number 5L93 [59]) using FATCAT (91, 92), resulting in optimized root mean square deviations (RMSD) of 2.75 Å for the NTD domains and 1.94 Å for the CTD domains. While this report was in the final stages of review, a structure of the full FIV CA protein was published (PDB accession number 5NA2 [93]). Our RELIK-based model for FIV CA-NTD fits well with the newly published FIV CA model, with alignment of the RELIK-based CA-NTD structure and the newly published FIV CA-NTD structure resulting in an RMSD of 2.67 Å using FATCAT.…”
Section: Construction Of Proviral and Codon-optimized Fiv Gag Plasmidmentioning
confidence: 99%
“…The FIV CA-NTD model obtained from SWISS-MODEL and the FIV CA-CTD crystal structure (PDB accession number 5DCK [18]) were separately aligned with HIV-1 CA structure (PDB accession number 5L93 [59]) using FATCAT (91, 92), resulting in optimized root mean square deviations (RMSD) of 2.75 Å for the NTD domains and 1.94 Å for the CTD domains. While this report was in the final stages of review, a structure of the full FIV CA protein was published (PDB accession number 5NA2 [93]). Our RELIK-based model for FIV CA-NTD fits well with the newly published FIV CA model, with alignment of the RELIK-based CA-NTD structure and the newly published FIV CA-NTD structure resulting in an RMSD of 2.67 Å using FATCAT.…”
Section: Construction Of Proviral and Codon-optimized Fiv Gag Plasmidmentioning
confidence: 99%
“…The recent determination of the crystal structure of the FIV CA has revealed that the molecule displays the standard α-helical CA topology with two domains separated by a linker [ 77 ] ( Figure 4 ). However, the crystallized FIV CA shows some features that differ from known structures of lentiviral CA proteins [ 78 , 79 ], such as the formation of a β-hairpin motif at its amino terminal end in the absence of a proline residue at position 1 and the presence of a cis Arg89-Pro90 bond [ 77 ]. It has been reported that the FIV CA binds the peptidyl-prolyl cis - trans isomerase cyclophilin A (CypA) [ 80 ].…”
Section: Role Of the Fiv Gag Domains In Virion Assembly And Buddinmentioning
confidence: 99%
“…Moreover, a recent study identified residues of the FIV capsid, which are important for FIV capsid assembly and are located in helix 4. Although our compounds do not bind directly to these two residues, these compounds could change the conformation of this region upon binding, resulting in the inhibition of p24:p24 interactions during capsid assembly [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The FIV CA protein was expressed and purified mostly as described [ 35 , 39 ]. Escherichia coli cells (BL2I (DE3) pLysS, Lucigen, Middleton, WI, USA) transformed with pRSET-p24EDCP-T were grown in Lysogenic broth medium (Sigma-Aldrich, Saint-Quentin-Fallavier, France), supplemented with 50 mg/mL of ampicillin, at 37 °C.…”
Section: Methodsmentioning
confidence: 99%